How Do We Start Palliative Care for Patients With End-Stage Liver Disease?. (13th March 2022) - Kim, Sookyung; Lee, Kyunghwa; Kim, Changhwan; Choi, Jahyun; Kim, Sanghee
Abstract : Patients with end-stage liver disease undergo repetitive patterns of recovery and deterioration and are burdened with uncertainty. Although quality of life is low in patients with end-stage liver disease and their family members, few studies have been conducted to identify what palliative care should be provided for them. This integrative review aimed to explore palliative care for patients with end-stage liver disease, focusing on the components and outcome measurements for further research. After searching for studies on palliative care for end-stage liver disease published between 1995 and 2017, 12 studies that met the inclusion criteria were analyzed. The common components of palliative care for patients with liver disease were: (a) an interdisciplinary approach, (b) early palliative care, (c) discussion goals of care with patient and family members, (d) symptom management, and (e) psychosocial support. It was reported that patients who were provided palliative care had improved itching, well-being, appetite, anxiety, fatigue, and depression, increased the number of do-not-resuscitate orders, palliative care consultations, and decreased length of stay. These findings could guide the development of palliative care for end-stage liver disease patients.